Scintigraphic evaluation of colonic transit in children with constipation using 67Ga-citrate - José Manzzini Calegaro; João Tajra; Janaína Souto; Flávia Marciano; Danielle De Landa; Sung Bae; Hélio Filho (World Journal of Nuclear Medicine)
The aim of this study was to assess the colonic transit in children and teenagers with chronic constipation. Twenty patients from 1.5 to 16 years old were included (mean age = 6.9 years). Chronic constipation etiologies were as follows: congenital megacolon in 6; surgical treatment in 5 (imperforate anus 2, hip dysplasia 1, sacral teratoma 1, and paraspinal neuroblastoma 1); idiopathic chronic constipation in 5; sacral myelomeningocele in 3; and intestinal duplication in 1. Static images on the anterior projection of the abdomen were performed 1, 6, 24, 48, and 72 h after the radiotracer oral administration. Doses were 3.7 MBq of 67Ga-citrate. The images were visually analyzed and classified by the observers as normal, diffuse slow transit, right slow transit, and left slow transit. Patients' dosimetric estimation was performed also. There were four cases of diffuse slow transit that responded well to the clinical treatment, 3 of them being chronic idiopathic constipation. From five patients with right slow transit, 4 were submitted to appendicostomy (Malone surgery) with good results. There were 11 cases of left slow transit (ten at the rectosigmoid level). Five of the 6 patients with congenital megacolon had left slow transit. Patients' dose estimation was 1.9 mSv to the whole body, 1.8 mSv to the ovaries, and 1.4 mSv to the testicular. This method is simple, safe, noninvasive, provides helpful functional information, and allows therapeutic decision regarding chronic constipation.